Maternal Protein Restriction Modulates Angiogenesis and AQP9 Expression Leading to a Delay in Postnatal Epididymal Development in Rat - de Mello Santos, Talita [UNESP]; Cavariani, Marilia Martins [UNESP]; Pereira, Dhrielly Natália [UNESP]; Schimming, Bruno César [UNESP]; Chuffa, Luiz Gustavo de Almeida [UNESP]; Domeniconi, Raquel Fantin [UNESP] (MDPI, 2019)
The maternal nutritional status is essential to the health and well-being of the fetus. Maternal protein restriction during the perinatal stage causes sperm alterations in the offspring that are associated with epididymal dysfunctions. Vascular endothelial growth factor (VEGF) and its receptor, VEGFr-2, as well as aquaporins (AQPs) are important regulators of angiogenesis and the epididymal microenvironment and are associated with male fertility. We investigated the effects of maternal protein restriction on epididymal angiogenesis and AQP expression in the early stages of postnatal epididymal development. Pregnant rats were divided into two experimental groups that received either a normoprotein (17% protein) or low-protein diet (6% protein) during gestation and lactation. At postnatal day (PND)7 and PND14, male offspring were euthanized, the epididymides were subjected to morphometric and microvascular density analyses and to VEGF-A, VEGF-r2, AQP1 and AQP9 expression analyses. The maternal low-protein diet decreased AQP9 and VEGFr-2 expression, decreased epididymal microvascularity and altered the morphometric features of the epididymal epithelium; no changes in AQP1 expression were observed at the beginning of postnatal epididymal development. Maternal protein restriction alters microvascularization and affects molecules involved in the epidydimal microenvironment, resulting in morphometric alterations related to a delay in the beginning of epididymis postnatal development.
Keywords: aqp1; aqp9; epididymal development; fetal programing; protein restriction; vegf